Encyclopedia of renewable and sustainable materials - Hashmi, Saleem; Choudhury, Imtiaz Ahmed (Elsevier, 2020)
"Encyclopedia of Renewable and Sustainable Materials, Five Volume Set provides a comprehensive overview, covering research and development on all aspects of renewable, recyclable and sustainable materials. The use of renewable and sustainable materials in building construction, the automotive sector, energy, textiles and others can create markets for agricultural products and additional revenue streams for farmers, as well as significantly reduce carbon dioxide (CO2) emissions, manufacturing energy requirements, manufacturing costs and waste. This book provides researchers, students and professionals in materials science and engineering with tactics and information as they face increasingly complex challenges around the development, selection and use of construction and manufacturing materials." - Publisher title screen